2019
DOI: 10.1111/cpr.12632
|View full text |Cite
|
Sign up to set email alerts
|

Non‐coding RNA MFI2‐AS1 promotes colorectal cancer cell proliferation, migration and invasion through miR‐574‐5p/MYCBP axis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited. AbstractObjective: Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) play essential roles in the tumour progression. LncRNAs mostly act as competing endogenous RNAs (ceRNAs) by sponging miRNAs. This study aimed to study the association of a novel lncRNA MFI2-AS1 with miR-574-5p/MYCBP axis in the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…For example, Xu et al reported that lncRNA TUSC7 functioned as a miR-211 decoy in the regulation of CDK6SH3 and suppressed the proliferation of CRC cells [16]. Li et al exhibited that lncRNA MFI2-AS1 regulated CRC cell proliferation, metastasis, cell cycle distribution, and apoptosis through competitively interacting with miR-574-5p to upregulate MYCBP expression [17]. Shi et al found that ZNFX1-AS1 served as a ceRNA to upregulate EZH2 expression by sponging miR-144 to promote CRC progression [18].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xu et al reported that lncRNA TUSC7 functioned as a miR-211 decoy in the regulation of CDK6SH3 and suppressed the proliferation of CRC cells [16]. Li et al exhibited that lncRNA MFI2-AS1 regulated CRC cell proliferation, metastasis, cell cycle distribution, and apoptosis through competitively interacting with miR-574-5p to upregulate MYCBP expression [17]. Shi et al found that ZNFX1-AS1 served as a ceRNA to upregulate EZH2 expression by sponging miR-144 to promote CRC progression [18].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xu et al has reported that lncRNA TUSC7 functions as a miR-211 decoy in the regulation of CDK6SH3 and suppresses the proliferation of CRC cells [28]. Li et al has exhibited that lncRNA MFI2-AS1 regulates CRC cell proliferation, metastasis, cell cycle distribution, and apoptosis through competitively interacting with miR-574-5p to upregulate MYCBP expression [29]. Shi et al nds that ZNFX1-AS1 serves as a ceRNA to upregulate EZH2 expression by sponging miR-144 to promote CRC progression [30].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are short RNAs that can be regulated by the sponge role of lncRNA, following by modulating the expression of the downstream genes by targeting their 3′untranslated regions (3′UTR) [35]. An increasing number of studies has demonstrated that miR-574-5p can be sponged by lncRNA, like lncRNA PTCSC3 and lncRNA MFI2-AS1, to modulate growth and metastasis of cancer cells [36,37]. In addition, miR-770-5p has been found to be downregulated by lncRNA TPT1-AS1 and correspondingly upregulated the expression of STMN1, leading to promotion of the proliferation of Glioma cells [38].…”
Section: Discussionmentioning
confidence: 99%